Country-specific dietary shifts to mitigate climate and water crises. (May 2020) - Kim, Brent F.; Santo, Raychel E.; Scatterday, Allysan P.; Fry, Jillian P.; Synk, Colleen M.; Cebron, Shannon R.; Mekonnen, Mesfin M.; Hoekstra, Arjen Y.; de Pee, Saskia; Bloem, Martin W.; Neff, Roni A.; Nachman, Keeve E.
Highlights: Country of origin accounted for a large share of the variation among diet footprints. Reducing animal foods in general was more climate-friendly than eliminating meat. Eating low on the food chain was comparable to vegan for GHG and water footprints. Pond-raised aquatic animals were by far the most blue water-intensive foods. Meeting both sustainability and health goals required more ambitious dietary shifts. Abstract: Undernutrition, obesity, climate change, and freshwater depletion share food and agricultural systems as an underlying driver. Efforts to more closely align dietary patterns with sustainability and health goals could be better informed with data covering the spectrum of countries characterized by over- and undernutrition. Here, we model the greenhouse gas (GHG) and water footprints of nine increasingly plant-forward diets, aligned with criteria for a healthy diet, specific to 140 countries. Results varied widely by country due to differences in: nutritional adjustments, baseline consumption patterns from which modeled diets were derived, import patterns, and the GHG- and water-intensities of foods by country of origin. Relative to exclusively plant-based (vegan) diets, diets comprised of plant foods with modest amounts of low-food chain animals (i.e., forage fish, bivalve mollusks, insects) had comparably small GHG and water footprints. In 95 percent of countries, diets that only included animal products for one meal per day were less GHG-intensive than lacto-ovo vegetarian diets (in which terrestrial and aquatic meats were eliminated entirely) in part due to the GHG-intensity of dairy foods. The relatively optimal choices among modeled diets otherwise varied across countries, in part due to contributions from deforestation (e.g., for feed production and grazing lands) and highly freshwater-intensive forms of aquaculture. Globally, modest plant-forward shifts (e.g., to low red meat diets) were offset by modeled increases in protein and caloric intake among undernourished populations, resulting in net increases in GHG and water footprints. These and other findings highlight the importance of trade, culture, and nutrition in diet footprint analyses. The country-specific results presented here could provide nutritionally-viable pathways for high-meat consuming countries as well as transitioning countries that might otherwise adopt the Western dietary pattern.